(3GdEHGfI aj GdMb def hdi TjFkG ef CehQ GdNdbs - (3eMeO Hf CHj HcQ Hf Ydj GdTWj GdUGdMj,J (B749 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eGdc Gdedc hHYO agPG cJGH GNJUQJg ef cJGH GdhXGFa GdeYQhaI ddefGbH GdehUhaI GPi CdaI GdNVQ Hf CHj HcQ Hf CMeO Gdedc GdeYR s
(3BNQgG (B:s
(3gcPG bjd aef Tcd ai TF ef Pdc ajLQHI aEf UM agh UMjM hEdG agh HGWd s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3GdfSNI HgG JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3YGQa MceJ (B- (3eQcR GdHMK GdYdei (B- (3Ge GdbQi s
Keywords: (3eJaQbGJs